A VirB4 ATPase of the mobile accessory genome orchestrates core genome-encoded features of physiology, metabolism, and virulence of Pseudomonas aeruginosa TBCF10839 - Wiehlmann, Lutz; Klockgether, Jens; Hammerbacher, Anna-Silke; Salunkhe, Prabhakar; Horatzek, Sonja; Munder, Antje; Peilert, Janno Florian; Gulbins, Erich; Eberl, Leo; Tümmler, Burkhard (Frontiers in Cellular and Infection Microbiology, 2023)
Pseudomonas aeruginosa TBCF10839 is a highly virulent strain that can persist and replicate in human neutrophils. Screening of a signature-tagged mutagenesis (STM) TBCF10839 transposon library in phagocytosis tests identified a mutant that carried the transposon in the VirB4 homolog 5PG21 of an integrative and conjugative element (ICE)-associated type IV secretion system of the pKLC102 subtype. 5P21 TBCF10839 insertion mutants were deficient in metabolic versatility, secretion, quorum sensing, and virulence. The mutants were efficiently killed in phagocytosis tests in vitro and were avirulent in an acute murine airway infection model in vivo. The inactivation of 5PG21 silenced the rhl, las, and pqs operons and the gene expression for the synthesis of hydrogen cyanide, the antimetabolite l-2-amino-4-methoxy-trans-3-butenoic acid, and the H2- and H3-type VI secretion systems and their associated effectors. The mutants were impaired in the utilization of carbon sources and stored compounds that are not funneled into intermediary metabolism. This showcase demonstrates that a single gene of the mobile accessory genome can become an essential element to operate the core genome-encoded features of metabolism and virulence.